Image guided surgery in the management of head and neck cancer. (June 2016) - Iqbal, Hassan; Pan, Quintin
Highlights: Fluorescent dyes should possess certain properties to build an optimal image with appropriate resolution to visualize tumor cells in real-time. Various imaging systems are available commercially but need to be refined to allow better tumor visualization and signal penetrance depth. Near-infrared fluorescence-guided optical imaging is an emerging technology that has high potential to impact the surgical management of head and neck cancer. Summary: Complete resection of head and neck tumors relies on palpation and visual inspection. Achieving a negative margin in remote locations in the head and neck region, especially in close proximity to critical structures, is often difficult to achieve. Positive resection margins in head and neck cancer are at high risk to develop recurrent disease and associated with poor prognosis. Near-infrared fluorescence-guided optical imaging is an emerging technology with the potential to move the surgical field forward and facilitate surgeons to visualize tumors in real-time intra-operatively. In this review, our focus is to discuss the recent advances and the potential application of near infrared (NIR) fluorescent-guided surgery in the management of head and neck cancer.